SISTEM PAKAR DIAGNOSIS PENYAKIT ISPA DENGAN METODE FORWARD CHAINING - irman efendi (AMIK Mitra Gama, 2022)
The progress of science and technology and its application in all fields can not be separated from the role of computer. In the field of health are many who use it to meet health services, to support operational activities for example in the field of ARD disease diagnosis. Computers today are very important, therefore the authors will try to design a disease diagnosis program, especially regarding acute respiratory infectious diseases based on computers to improve health services. The program will use one of the branches of AI (Artificial Intellegence) ie Expert System with Forward Chaining method, because the branch can represent kemam puan computer program that can mimic the thoughts and knowledge of an expert to solve a problemKeywords: Sistem Pakar, Forward Chaining, ISPA